Identitarian valences in Xoguetes pra un tempo prohibido, by Carlos Casares - Fernández Vázquez, Mar (Madrygal. Revista de Estudios Gallegos, 2011)
This paper examines the identity valences of Xoguetes pra un tempo prohibido, and it stands out Carlos Casares’ contributions to the conformation of Galician literary system.